Red-Listed Ecosystem Status of Interior Wetbelt and Inland Temperate Rainforest of British Columbia, Canada - Dominick A. DellaSala; James R. Strittholt; Rebecca Degagne; Brendan Mackey; Jeffery R. Werner; Michelle Connolly; Darwyn Coxson; Andrew Couturier; Heather Keith (Land, 2021)
The Interior Wetbelt (IWB) of British Columbia, which includes the globally rare Inland Temperate Rainforest (ITR), contains primary forests poorly attributed and neglected in conservation planning. We evaluated the IWB and ITR using four IUCN Red List of Ecosystems Criteria: geographic distribution, environmental degradation (abiotic and biotic factors), and likelihood of ecosystem collapse. Clearcut logging (3.2M ha) represented 57% of all anthropogenic disturbances, reducing potential primary forest by 2.7 million ha (28%) for the IWB and 524,003 ha (39%) for the ITR. Decadal logging rates nearly doubled from 5.3% to 10.2% from 1970s–2000s. Core areas (buffered by 100-m from roads and developments) declined by 70% to 95% for the IWB and ITR, respectively. Vulnerable was assigned to karst, the only abiotic factor assessed, because it was associated with rare plants. For biotic factors, Old-Growth Birds were Vulnerable, Southern Woodland Caribou (Rangifer tarandus caribou) habitat and Sensitive Fish were Endangered, and Old-Growth Lichens habitat was Critical. Overall, the IWB was ranked as Endangered and the ITR as Critical with core area collapse possible within 9 to 18 years for the ITR, considered one of the world’s most imperiled temperate rainforests.